The main determinants of bank profitability in China - Liu, Qi (2018)
This dissertation empirically examines the determinants of bank profitability in China over the period 2011 to 2017. In this dissertation, return on average assets (ROAA) and net interest margin (NIM) are chosen as profitability measures. Independent variables are divided into bank-specific variables, industry-specific variables and macro-economic variables. Using unbalanced panel data, which contain 201 commercial banks and two-step system GMM estimator, the results obtained indicate that cost efficiency, banking sector development, stock market development, market concentration and inflation have a positive effect on bank performance, while bank size tends to be negatively related to bank profits. Besides, credit risk and bank diversification are shown to be determining factors in explaining bank profitability in China.